The safety, tolerability, and efficacy of a liquid formulation of deferiprone in young children with transfusional iron overload - El Alfy, M.; Sari, T.T.; Lee, C.L.; Tricta, F.; El-Beshlawy, A. (Lippincott, Williams & Wilkins, 2010)
Limited data are available on the use of deferiprone in children younger than 10 years of age. This study evaluated the safety and efficacy of a new liquid formulation of deferiprone for the treatment of transfusional iron overload in children 1-10 years old. One hundred children (91 thalassemia major, 8Hb E-beta thalassemia, and 1 sickle cell disease) were enrolled for a 6-month treatment with deferiprone (50 to 100 mg/kg/d). The safety profile was similar to or better than that reported in earlier studies with deferiprone tablets in older children and adults. No unexpected adverse reactions were observed. Gastrointestinal intolerance (GI) was observed in 11% and an increased serum ALT in 12% of the children. Both events were transient. Mild neutropenia, observed in 6% of patients, did not progress to agranulocytosis and resolved despite continuous deferiprone treatment. Two patients experienced agranulocytosis that resolved without complications upon discontinuation of therapy. Deferiprone use was associated with a significant decline in mean serum ferritin level from 2532 +/- 1463 mu g/L at baseline to 2176 +/- 1144 mu g/L (P < 0.0005). The results of this study show a favorable benefit/risk ratio of deferiprone oral solution for the treatment of young children with transfusional iron overload.